Ameliorative effect of different doses of MgNH4PO4•6H2O precipitate recovered from the effluent of UASB treating poultry manure wastewater: Growth of Lolium perenne - Yetilmezsoy, Kaan; Sertyesilisik, Begum; Kocak, Emel; Sapci-Zengin, Zehra (WFL PUBL, 2009)
The ameliorative effect of different doses of MgNH4PO4 center dot 6H(2)O (MAP) precipitate was investigated in a series of lab-scale experiments. The high strength of ammonium nitrogen was first recovered from the effluent of up-flow anaerobic sludge blanket (UASB) treating poultry manure wastewater (PMW) using different combinations of chemicals. Previous results indicated that maximum NH4+-N removal was obtained as 85.4% at pH 9.0 with the addition of MgCl2 center dot 6H(2)O + KH2PO4 at the stoichiometric ratio (Mg2+:NH4+-N:PO43--P = 1:1:1). Following to MAP precipitation tests, three quick-growth plants including purslane, garden cress and grass were tested to explore the ameliorative effect of the MAP precipitate obtained under the optimum conditions. Results of the first stage greenhouse experiments showed that the rates of increase in fresh and dry weights, as well as in fresh height of grass grown in the garden soil were about 257, 402 and 156% for MAP as compared with control, respectively. Since the growth rates of grass in terms of both measured weights and height were found to be superior than other types of test plants, grass was selected as the model plant for the further agricultural experiments conducted in this study A total of 7 pots, including the control, were set up in parallel with different MAP/seed ratios ranging from 1-10 (g/g) for cultivation of grass. Results demonstrated that over-dosing of MAP in the garden soil did not cause any inhibition of sprouting or burning effect on the growth of grass, due to its limited solubility in water. Apart from the agricultural research, physical and fire-retardant properties of the recovered MAP precipitate used in the experiments were also presented as a part of this investigation.
Keywords: Up-flow anaerobic sludge blanket; poultry manure wastewater; ammonium nitrogen; magnesium ammonium phosphate (MAP); Lolium perenne; PHYSICOCHEMICAL TREATMENT; STRUVITE CRYSTALLIZATION; REMOVING PHOSPHORUS; LANDFILL LEACHATE; PHOSPHATE; AMMONIUM; NITROGEN; COD; Food Science & Technology